Bald Eagle space use in an urbanizing landscape - Middleton, Miranda, author; Pejchar, Liba, advisor; Conrey, Reesa, committee member; Boone, Randall, committee member (Colorado State University. Libraries, 2024)
Rapid human population growth has led to an increase in urbanization globally. Urbanization extends beyond the boundaries of city limits to include the conversion of natural areas into energy production (such as coal, solar, and wind), the damming and diversion of rivers, and agriculture and forestry to feed and house urban residents. This land use change is a major driver of biodiversity loss and significantly impacts wildlife space use. While many species are unable to persist in urban environments, some species of raptors are frequently found using the urban matrix. Bald Eagles (Haliaeetus leucocephalus) are an iconic North American species that was once near extinction but are now commonly observed in and around cities. Here, I examined how urbanization influenced Bald Eagle home range size and habitat selection in the northern Front Range of Colorado, a semi-arid region currently experiencing rapid growth in both eagle and human populations. In my first chapter, I investigated home range size and core-use areas of 24 territorial Bald Eagles affixed with a GPS/GSM transmitter. Specifically, I examined home range size and core-use area at five different nest stages of the annual cycle (pre-nesting, incubation, nestling, post-fledge, and non-nesting) and for both sexes. Home ranges and core-use areas were created using a dynamic Brownian bridge movement model. I then used a mixed-effects linear regression model to identify the land cover characteristics influencing these areas. My research shows that Bald Eagle home ranges and core-use areas vary in size and are often discontinuous, frequently containing one to three separate areas. Home ranges were fifteen times or more larger than core-use areas. Smaller home ranges were positively correlated with water, herbaceous wetlands, and human development while greater canopy cover was associated with larger home ranges. Similarly, water was positively associated with smaller core-use areas while greater canopy cover was associated with larger core-use areas. Home ranges and core-use areas tended to be larger during the pre-nesting and non-nesting stages and smaller during the nestling and post-fledge stages, with these differences being more pronounced in females. Male home ranges were smallest during the post-fledge stage (43.89 km2 ± 98.67) and largest during the non-nesting stage (117.31 km2 ± 177.04). Females generally had smaller home ranges, which were smallest during the nestling stage (2.86 km2 ± 2.14) and largest during the incubation stage (70.31 km2 ± 183.48). In Chapter One, I mapped eagle home ranges throughout the annual cycle and analyzed what habitat features are associated with smaller home ranges, which may indicate higher quality habitat. In my second chapter I built on these findings to assess habitat selection within and beyond the home ranges calculated in chapter one. To examine habitat selection I used a logistic regression model during the same five nest stages, for both sexes, and at two different scales: within home range and within study area. My findings indicate that Bald Eagle habitat selection is influenced by nest stage, sex, spatial scale, land cover, and human development. Generally, eagles selected for herbaceous wetlands, grasslands, and habitats near water. They avoided agriculture and dense canopy cover. Overall eagles avoided development; however, they used low to moderately developed landscapes when in close proximity to water. Eagles had a higher probability of using developed areas within their home range than within the study area and during the incubation and nestling stages. Female eagles were also more likely to use developed areas than male eagles. At all nest stages, eagles were more likely to use areas with low levels of development than areas with high levels of development. My findings suggest that the space-use patterns of Bald Eagles are complex and vary throughout the annual cycle. Eagles are capable of thriving in urban environments, where their smaller home ranges suggest that they can find quality habitat. Conservation efforts in urbanizing regions should focus on protecting habitats close to water, in herbaceous wetlands, and with open canopy cover. It is also important to recognize that while Bald Eagles readily use urban environments with these habitat features, they prefer areas with low to moderate development. Additionally, conservation strategies should account for the fact that Bald Eagles have disconnected home ranges with critical foraging sites located away from their nests. Together, these recommendations could help guide policy and practice for sustaining Bald Eagle populations during their full annual cycle in urbanizing landscapes.
Keywords: habitat selection; urbanization; home range; Bald Eagle